Analytical comparison of traffic noise indices—A case study in District 14 of Tehran City. Issue 3 (September 2016) - Nassiri, Parvin; Karimi, Elham; Monazzam, Mohammad Reza; Abbaspour, Majid; Taghavi, Lobat
Noise pollution is a growing concern of majority of people around the world. Accordingly, the present study was carried out to analyze, for the first time, traffic noise indices and to introduce an optimal noise index for road traffic noise. For this purpose, the District 14 of Tehran Metropolitan City was selected as a case study wherein a total number of 91 stations were selected so as to cover noise susceptible areas. The measurements were performed at three occasions of morning, noon, and evening. In order to estimate the traffic noise index, noise pollution level, and noise impact index, the L10, L50, and L90, were recorded at each station with 40 replicates. According to the obtained results, among different land uses in the study area, the maximum and minimum traffic noise index values of 113.7 dBA and 50.1 dBA were reported from educational land use. The highest noise pollution level of 96.8 dBA was measured at the educational land use while the lowest noise pollution level of 65 dBA was recorded at the medical land use. The noise impact index value was estimated at 1.5 for the entire region indicating noise level is much higher than the acceptable threshold for residents. Overall, noise pollution level would be a better index when the objective is to measure the overall noise pollution condition in the study area, whereas it gives much more weight to the difference between the ambient and peak noise levels. However, in situations where traffic-induced noise measurement is required, the traffic noise index seems more appropriate. Further, the noise impact index would be more useful to quantify the effect of noise pollution on exposed people.